Genetic and pharmacological inactivation of astroglial connexin 43 differentially influences the acute response of antidepressant and anxiolytic drugs. (16th January 2020) - Portal, Benjamin; Delcourte, Sarah; Rovera, Renaud; Lejards, Camille; Bullich, Sebastien; Malnou, Cécile E.; Haddjeri, Nasser; Déglon, Nicole; Guiard, Bruno P.
Abstract: Aim: Astroglial connexins (Cxs) 30 and 43 are engaged in gap junction and hemichannel activities. Evidence suggests that these functional entities contribute to regulating neurotransmission, thereby influencing brain functions. In particular, preclinical and clinical findings highlight a role of Cx43 in animal models of depression. However, the role of these proteins in response to currently available psychotropic drugs is still unknown. Methods: To investigate this, we evaluated the behavioural effects of the genetic and pharmacological inactivation of Cx43 on the antidepressant‐ and anxiolytic‐like activities of the selective serotonin reuptake inhibitor fluoxetine and the benzodiazepine diazepam, respectively. Results: A single administration of fluoxetine (18 mg/kg; i.p.) produced a higher increase in hippocampal extracellular serotonin levels, and a greater antidepressant‐like effect in the tail suspension test in Cx43 knock‐down (KD) mice bred on a C57BL/6 background compared to their wild‐type littermates. Similarly, in outbred Swiss wild‐type mice, the intra‐hippocampal injection of a shRNA‐Cx43 or the acute systemic injection of the Cxs inhibitor carbenoxolone (CBX: 10 mg/kg; i.p.) potentiated the antidepressant‐like effects of fluoxetine. Evaluating the effects of such strategies on diazepam (0.5 mg/kg; i.p.), the results indicate that Cx43 KD mice or wild‐types injected with a shRNA‐Cx43 in the amygdala, but not in the hippocampus, attenuated the anxiolytic‐like effects of this benzodiazepine in the elevated plus maze. The chronic systemic administration of CBX mimicked the latter observations. Conclusion: Collectively, these data pave the way to the development of potentiating strategies in the field of psychiatry based on the modulation of astroglial Cx43.